THE VOICES OF THE AFRO-AMERICAN IN LITERATURE: A STUDY ON SLAVERY - Femmy Dahlan (Celt: A Journal of Culture, English Language Teaching & Literature, 2008)
Literary work could portray both the life from the real world and also functions as a media to voice the injustice experienced by certain society. Slavery in America can be seen through three literary works written by Afro-American writers. These three writers describe how slavery had destroyed the lives of the slaves in the Southern part of America. The slaves were treated cruelly by the owners which bring bitterness to them. The lives of the slaves at that time was full of torture both physically and mentally.